(untitled) (Journal of Vocational Innovation, Achievement and Education, 2025)
Corn (Zea mays L.) is a strategic food commodity that plays an important role as food, animal feed, and industrial raw materials. In its cultivation, fertilization is an important factor, however, conditions in the field show that agricultural practices still tend to be oriented towards increasing yields without considering sustainability aspects, often causing land degradation and decreasing productivity in the long term. Efforts to increase corn production need to be supported through the application of effective and sustainable fertilization, especially for composite corn. Objective: This study aims to determine the effect of fertilizer types on the growth of composite corn plants of Sukmaraga and Lamuru varieties, including granular organic fertilizer, NPK fertilizer, and a combination of granular organic fertilizer and NPK. Research Method: Using an experimental design with several fertilization treatments, namely without fertilizer (control), granular organic fertilizer, granular organic fertilizer + NPK, and NPK fertilizer. Parameters observed include plant height, number of leaves, stem diameter, and male and female flowering times. Data were analyzed using analysis of variance (ANOVA) and continued with an average comparison to determine differences between treatments. If a significant difference is found, a LSD test is carried out at the 5% level. Results and Discussion: Inorganic fertilizers provide the highest vegetative growth in composite corn, while organic fertilizers play a role in supporting soil fertility and the combination of both has the potential to increase growth while maintaining the sustainability of land productivity.